Cu/Fe dual atoms catalysts derived from Cu-MOF for Zn-air batteries. (August 2022) - Wang, Meimei; Gao, Peng; Li, Dongyan; Wu, Xiuping; Yang, Meng; Li, Zhaoqiang; Shen, Yuesong; Hu, Xiaohui; Liu, Youlin; Chen, Zhongwei
Abstract: The exploration of direct and effective strategies to construct catalysts with targeted active sites is highly desired. Herein, we report a self-template strategy to fabricate Cu/Fe dual-metal-atoms active sites anchored on MOF-derived porous carbon nanosheets (Cu/Fe/N–CNS). Well-defined Cu/Fe/N–CNS performs outstanding electrocatalytic ORR activity with half-wave potential (0.91 V) in alkaline solution, which outperforms commercial Pt/C catalyst. DFT computational studies indicate that Fe–N active sites on Cu/Fe/N–CNS are more favored than Cu–N active sites for the activation of O–O-containing intermediate products to further boost electrocatalytic activity. Furthermore, Cu/Fe/N–CNS exhibits superior discharge stability with negligible voltage fading over 20 cycles (∼150 h) at 15 mA cm −2 in primary Zn-air batteries. This strategy can open new avenues for the construction of superb dual-metal catalysts. Graphical abstract: Image 1 Highlights: Cu/Fe dual-metal-atoms are uniformly dispersed on porous carbon nanosheets. Cu, Fe/N–CNS exhibits an excellent ORR performance in alkaline media. DFT studies indicate that Fe–N active sites on Cu, Fe/N–CNS are more favored than Cu–N active sites. Cu, Fe/N–CNS reveals an outstanding discharge stability in primary Zn-air batteries.